Development of Economic E-Module on Money and Banking Material For Student - Lestasi, Nelvy Warsi Enggal (Classroom Action Research Journal (CARJO), 2019)
This research was implemented because of the burnout and boredom Economics students to receive lessons because teachers only use the lecture method without any other study variation and only rely on one textbook as a source of learning. Besides, many students are reluctant to read the textbook because the book is less interesting and too many posts. SMA Negeri 1 Panggul Trenggalek have been had some enough electronic facilities, but it not used optimally by the teachers in the learning process. The E-Module research and development model used is ADDIE model with five steps, that is analysis, design, development, implementation, and evaluation. In the development of this Economics E-Module involves the validation of material expert and media experts from Economics professors and lecturers who are competent in the learning media. Besides, the subject of a trial in this research is all students in Tenth Grade A that about 32 students. The result of the research and validation of material expert and media expert shows that the Economics E-Module on Money and Banking Material is fit for use. Based on the result of the pre-test and post-test that was given to students before and after using the Economic E-Module indicates that E-Module is effectively used to improve the students learning outcomes.Â KeywordsDeveloping, Economics E-Module, Money and Banking